Not just another quiet student: reducing participation imbalance through robot moderation - Asadi, Ali; Fischer, Kerstin (Frontiers in Education, 2025)
IntroductionDespite their many advantages, group activities can result in participation imbalance, especially when a participant joins the activity remotely. In this experimental study, we address the issue of imbalance in small groups, which consist of two co-situated participants and one remote student on a telepresence robot. The aim is to investigate whether using a robot to moderate group activities can affect engagement and balance participation.Methods84 participants were recruited and assigned to two conditions, namely baseline (without a robot moderator) and experimental (with a robot moderator). As participants engaged in completing a language learning task, the moderator implemented verbal and nonverbal interventions.ResultsData analysis shows that while nonverbal interventions mostly failed, verbal interventions had a success rate of 88.24% in encouraging participants to start speaking. Regarding the talking time of group members, results show significant differences between the mean scores in both conditions, indicating a more balanced participation of group members in the experimental condition. Participants also formed positive attitudes toward the robot moderator.DiscussionIn conclusion, using the robot moderator positively affected group dynamics by encouraging quiet participants to be more active and rendering the interaction to be more balanced.